Millennial Muslims and use of Cyber-Islam: a case study of Bilal Philips and Mufti Menk on Twitter and their Impacts - Cusi, Mariet Rosnaida Cabrera; Berghout, Abdul Aziz (IIUM Press, 2023)
This study attempts to use Big Data Analytic Techniques to investigate the views of Millennial Muslims on the effectiveness of scholars/preachers on cyber-Islam. Two eminent scholars, Bilal Philips, and Mufti Menk have been chosen for this purpose. It examines the changing expressions and manifestations of Islam because of historical epochs and contexts. For example, the modern world is in its "post-postmodernist" stage and context, which necessitates a rethinking of previous debates and discourses on Islam. The Millennial Age is discussed, as well as its characteristics and their implications for Muslim expression of Islam. Cyber-Islam is the study ofthe intersection of Islam and online platforms. There is a review of academic literature on Bilal Philips and Mufti Menk. This study's methodology is to incorporate data mining methods to create a framework that can be used effectively to analyze the Twitter content and followers of Bilal Philips and Mufti Menk from an Islamic perspective. The study reveals various facts about Millennial Muslims as well as the way Islamic knowledge is communicated via social media. The study concludes that combining social media studies with Islamic studies can provide a more complete picture of contemporary Muslims and their online engagement with Islam.